PENGABDIAN KEPADA MASYARAKAT DENGAN KEGIATAN MURAL UNTUK MEMPERCANTIK LAPANGAN ASTAGINA, PADANGSAMBIAN KLOD - Gede Lingga Ananta Kusuma Putra; I Gede Jaya Putra (Jurnal Lentera Widya, 2020)
Beautifying the environment is one form of our concern as creatures who depend on an environment to live. By beautifying an environment will create a comfortable impression and atmosphere to be in that environment. One of the actions that can beautify the environment is to do mural activities on walls or walls that are less attractive in appearance. Mural is an activity of painting or drawing on flat media, walls, walls or large surfaces that are permanent in nature. Based on the results of observations that have been made in the Astagina Field, which is located on Jl. Mt. Tangkuban Perahu No.291, Padangsambian Klod, Kec. Denpasar Bar., Denpasar City, Bali 80117, has one corner of the large wall that is unkempt and unattractive. So that the Bali Design and Business Institute will carry out mural creation activities in Astagina Field to beautify the environment as well as an embodiment of community service programs.